2015
DOI: 10.1080/08997659.2015.1088488
|View full text |Cite
|
Sign up to set email alerts
|

Flavobacterium psychrophilum Infections in Salmonid Broodstock and Hatchery‐Propagated Stocks of the Great Lakes Basin

Abstract: Bacterial coldwater disease (BCWD), caused by Flavobacterium psychrophilum, threatens wild and propagated salmonids worldwide and leads to substantial economic losses. In addition to being horizontally transmitted, F. psychrophilum can be passed from infected parents to their progeny, furthering the negative impacts of this pathogen. In Michigan, both feral and captive salmonid broodstocks are the gamete sources used in fishery propagation efforts. A 5-year study was initiated to follow the prevalence of syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…It is also interesting that for the feral fish in the GLB and in particular for Chinook salmon (which harbor the highest F. psychrophilum infection prevalence among the 3 Oncorhynchus spp. that were recently examined) (36), data from this study do not seem to indicate an epidemic population structure, as demonstrated by the lack of dominant STs or CCs. It is also only among these fish that we observed infections by the same ST (e.g., ST256) or CC (e.g., CC-ST256) in different fish host species.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…It is also interesting that for the feral fish in the GLB and in particular for Chinook salmon (which harbor the highest F. psychrophilum infection prevalence among the 3 Oncorhynchus spp. that were recently examined) (36), data from this study do not seem to indicate an epidemic population structure, as demonstrated by the lack of dominant STs or CCs. It is also only among these fish that we observed infections by the same ST (e.g., ST256) or CC (e.g., CC-ST256) in different fish host species.…”
Section: Discussioncontrasting
confidence: 65%
“…DNA was extracted from each suspected F. psychrophilum isolate using the DNeasy blood and tissue kit (Qiagen), according to the manufacturer's protocol for Gram-negative bacteria. For a portion of the isolates, the F. psychrophilum-specific primers of Toyama et al (39) were used to PCR amplify a partial stretch of the 16S rRNA gene as previously described (36). The remaining isolates were confirmed to be F. psychrophilum using PCR amplification with degenerate universal primers (40) and Sanger sequencing as previously reported (41).…”
mentioning
confidence: 99%
“…Bacterial genomic DNA was extracted using the DNeasy Blood and Tissue kit (Qiagen, Inc., Valencia, CA) according to the manufacure's protocol for Gram-negative bacteria, quantified using a Qubit fluorometer (Life Technologies, Grand Island, NY), and then diluted to 20 ng/l. Prior to MLST analyses, the identity of all isolates was confirmed as F. psychrophilum using the conventional PCR assay of Toyama et al (35) as detailed previously (36).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically for Flavobacterium psychrophilum, molecular confirmation was performed as previously described (Van Vliet et al. ).…”
Section: Methodsmentioning
confidence: 99%